ANALISIS MODEL SUPPLY CHAIN MANAGEMENT TERHADAP PRODUKTIVITAS PADA UMKM TEMPE DI KECAMATAN SINTANG - Ardiansyah Ardiansyah (Media Riset Bisnis Ekonomi Sains dan Terapan, 2023)
The aims of this study were 1) to analyze the supply chain model for tempe production SMEs, 2) to analyze the relationship between supply chain management and the productivity of tempe production SMEs. The type of research used is descriptive. The population in this study were tempe entrepreneurs, with a sample of 20 people. The sampling technique used is judgment sampling. Data analysis used stepwise regression analysis, forward selection, backward elimination.The results of the study show that the supply chain model in tempe production SMEs consists of several members, including: suppliers, inventories, producers, collectors, retailers and consumers. The results of the analysis of the relationship between supply chain management (suppliers, supplies, production, distributors, retailers, cooperation and labor) with productivity show that only one variable has a significant relationship, namely the cooperation variable.Keywords :Supply Chain Management, Productivity, Tempe